2022
DOI: 10.1136/neurintsurg-2021-018464
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of time-resolved whole brain flat panel detector perfusion imaging using RAPID ANGIO in patients with acute stroke: comparison with CT perfusion imaging

Abstract: BackgroundIn contrast to conventional CT perfusion (CTP) imaging, flat panel detector CT perfusion (FD-CTP) imaging can be acquired directly in the angiosuite.ObjectiveTo evaluate time-resolved whole brain FD-CTP imaging and assess clinically important qualitative and quantitative perfusion parameters in correlation with previously acquired conventional CTP using the new RAPID for ANGIO software.MethodsWe included patients with internal carotid artery occlusions and M1 or M2 occlusions from six centers. All pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…However, CTP rCBF <30% and FD‐CTP rCBF <45% showed a good correlation ( R 2 = 0.84). Illustrative examples of patients who suffer from middle cerebral artery (MCA) occlusion are shown in Figure 2 77 . Itokawa et al 78 confirmed the efficacy of CBCT perfusion in patients with AIS using the Siemens Healthcare “Artis zee biplane” device by comparing image quality and decision‐making confidence with those of MRI.…”
Section: Cbct Perfusion Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…However, CTP rCBF <30% and FD‐CTP rCBF <45% showed a good correlation ( R 2 = 0.84). Illustrative examples of patients who suffer from middle cerebral artery (MCA) occlusion are shown in Figure 2 77 . Itokawa et al 78 confirmed the efficacy of CBCT perfusion in patients with AIS using the Siemens Healthcare “Artis zee biplane” device by comparing image quality and decision‐making confidence with those of MRI.…”
Section: Cbct Perfusion Techniquementioning
confidence: 99%
“…Nicholson et al 76 believed that CBCT perfusion images (Philips X‐per CT) could provide an excellent addition to patients with AIS who intend to receive EVT therapy compared with MDCT perfusion. Kurmann et al 77 reported that the qualitative and overall quantitative perfusion results of time‐resolved whole‐brain FD‐CTP correlated well with conventional CTP, suggesting that establishing a direct‐to‐angio approach is feasible and increases the probability of a better clinical outcome. They acquired time‐resolved whole‐brain FD‐CTP datasets using a multiphase FD perfusion acquisition protocol (Syngo DynaCT Multiphase, Siemens Healthineers).…”
Section: Cbct Perfusion Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of flat panel detector CTP (FDCTP) source images, multiphase flat panel detector CTA (mFDCTA) and perfusion maps can be reconstructed. [8][9][10] This technology enables direct transport of patients to the angio suite ("direct-to-the angio" approach), which, in turn, can improve in-hospital workflows, reduce the time to treatment, and may ultimately increase the chances of good clinical outcome. [11][12][13][14][15][16] While collateral scores are well-validated in conventional multiphase CTA (mCTA)/CTP, data on the evaluation of the collateral status derived from FDCTP imaging is scarce.…”
mentioning
confidence: 99%